Indo-SAARC Trade Trend during COVID-19 Era - Sharma, Dr. Vipin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nations and territories in South Asia have been influenced by the covid-19 pandemic. The first South Asian nation to report an affirmed case was Nepal and India was the first South Asian nation to overwhelm China regarding the number of Covid-19 cases. The SAARC Intra-Regional Trade was at that point drifting around an extremely low level at less than 5 percent, the flare-up of Covid-19, further influenced the intra-regional trade in South Asia. The present study will examine India’s trade trend with the South Asian nation during the Covid-19 era. The South Asian countries are undergoing through covid-19 pandemic since November 2019. The empirical evidence shows that this has led to an increased India’s trade trend in these countries. Surprisingly, though the trade between India-SAARC has not grown substantially, there has been a change in the significance of India's trading partners over time